HRK inhibits colorectal cancer cells proliferation by suppressing the PI3K/AKT/mTOR pathway - Wang, Haowei; Chen, Yujia; Yuan, Qinzi; Chen, Lixia; Dai, Peiling; Li, Xuenong (Frontiers in Oncology, 2022)
Background As one of the most common malignant tumor, colorectal cancer (CRC) continues to have a high incidence and mortality rate. HRK belongs to the BCL-2 protein family, which has been shown to have antitumor effects in prostate cancer. However, its role in colorectal cancer is not yet known. Methods In this study, we verified the expression levels of HRK in colorectal cancer tissues by public database search as well as immunohistochemistry. Next, we analyzed HRK expression levels in CRC tissues,adjacent non-cancerous tissues, cell lines and normal intestinal epithelial cells by qPCR and Western blotting. CCK-8 proliferation assays, transwell assays, wound healing assays, colony assays and flow cytometry were performed to clarified the effect of HRK on CRC cells. Western blotting and rescue experiments were used to determine the role of HRK in regulating PI3K/AKT/mTOR signaling pathway. Results HRK expression was lower in CRC tissues and cell lines. Gain and loss of function experiments showed that HRK decreased proliferation, invasion and migration of CRC cells. Low expression of HRK inhibited CRC cell apoptosis as well as activated the PI3K/AKT/mTOR signaling pathway. In addition, rapamycin inhibits the activation of PI3K/AKT/mTOR signaling pathway and reverses HRK-induced alterations in cell biological functions. Conclusion Our study demonstrates that HRK is lowly expressed in colorectal cancer tissues. And for the first time, HRK was shown to promote apoptosis and inhibit proliferation of colorectal cancer cells by inhibiting PI3K/AKT/mTOR signaling pathway. HRK represents a potential target for the treatment of CRC.